Physical fitness related to motor performance and health of adolescents of the southwest region of the state of Sao Paulo and north pioneer of the state of Parana - Bandeira Lima, Flavia Evelin; Coco, Mariane Aparecida; Pellegrinotti, Idico Luiz [UNESP]; Lima, Walcir Ferreira; Lima, Silvia Bandeira; Lima, Fellipe Bandeira (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2018)
Introduction: Each human being has a behavior with unique and complex characteristics, which in their development over the years, individually modify the physical fitness (Pereira and collaborators, 2014). Objective: In this way, the objective of the study was to verify the physical fitness related to the motor performance and the health of adolescents between 12 and 15 years of the southwestern region of the State of Sao Paulo and Pioneer North of Parana. This is a descriptive quantitative research with a cross-sectional methodological design, approved by the CEP-UNIMEP Research Ethics Committee by ethical opinion n degrees 113/2015. The sample consisted of 387 students between 12 and 15 years, enrolled in public schools. The PROESP-Br (Proesp-Br, 2016) protocol was used to carry out the tests. After the data collection, the data were submitted to statistical analysis. Results and Discussion: It was verified that in the anthropometric indicators a large part of the sample was considered to be overweight and in the health risk zone. Nevertheless, poor motor classification and low level of physical activity for both sexes. In a similar study (Mello and collaborators, 2015) it was analyzed that the results indicated high frequencies of adolescents with weak motor performance, certifying the findings in this research. Conclusion: It was concluded that, regarding the nutritional status, the results presented by the adolescents were not satisfactory for the preservation of a healthy lifestyle. And, the low level of physical activity corroborates for the decline in physical fitness related to performance and health.
Keywords: Physical fitness; Adolescents; Performance; Health